(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Analysis of scientific studies on the mechanism of paraffin deposits formation in the wells is performed. An important advantage of MAU-1 (magnetic anti-paraffin unit) is the use of plugs of a nonmagnetic material placed on the outer surface of the radially magnetized magnets is the ability to use compound, taken from individual sectors or from elements of another form of radially magnetized magnets using the most modern magnetic materials with rare-earth metals, that allows to increase more the amplitude and gradient of strength affecting on the fluid of a magnetic field and thereby to improve the efficiency of the device for magnetic field conditioning. Magnetic oil treatment the authors suggest as a separate method of paraffin control deposition at it transporting by pipelines.